Development of the fire retardant glass fabric/carbonized phenolic composite. (15th July 2016) - Kim, Minkook; Choe, Jaeheon; Lee, Dai Gil
Abstract: Because fiber reinforced polymeric composite materials have the advantages of high specific strength and stiffness, their potential for replacing concrete, aluminum and steel. However, the poor fire resistance of fiber reinforced polymeric composite materials is one of the obstacles for their applications. In this study, a fire retardant glass fabric/carbonized phenolic composite was developed using the carbonization of the phenolic resin. Although the glass fiber is not combustible, it melts at approximately 800°C on exposure to fire, whereas the phenolic resin has good fire resistance with minimum smoke levels, excellent dimensional stability and thermal strength. Moreover, the phenolic resin is carbonized at high temperature (above 500°C), which prevents the spread of flames. However, shrinkage during the carbonization process weakens its strength and stiffness. To improve the pristine- and post-fire mechanical properties of the glass fabric/phenolic composite, flame and silane treatments were applied to the glass fabrics. The carbonization and impregnation of the phenolic resin matrix of the composite was repeated several times to develop the glass fabric/carbonized phenolic composite, from which the post-fire tensile strength and the carbonized phenol matrix ratio were measured with respect to the number of carbonization processes.